Self-regulation, motivation and quality of life of accounting students in remote education (Revista Brasileira de Contabilidade e Gestão, 2022)
Objective: To analyze how the use of self-regulated learning practices, the level of motivation in learning, and quality of life are correlated. Method: A quantitative and descriptive research was conducted by applying a questionnaire to 217 accounting undergraduates enrolled in four higher education institutions (HEIs) at Paraná. Results: Students reported feeling little motivated to study during remote education due to COVID-19 and experiencing relatively high levels of negative feelings (such as bad mood, anxiety, and/or depression). As for self-regulated learning strategies, “self-evaluation” and “self-consequence” were, respectively, the most and least used. Statistical correlations showed that student motivation is strongly correlated with quality-of-life factors such as “ability” and “concentration” to study, and these, in turn, were the items most correlated with self-regulated learning strategies. Contributions: These results highlight the importance of increasingly stimulating autonomous learning by using teaching approaches that promote motivation, reducing the levels of negative feelings.
Keywords: accounting sciences students; remote learning; self-regulation; self-regulated learning strategies; Covid-19; motivation; quality of life